Implementasi Modul Proyek Penguatan Profil Pelajar Pancasila Kurikulum Merdeka Di SDN Telaga Biru 4 Banjarmasin - Radhaina, Jannatul; Mutia, Mutia; Khairiyati, Nurlaila Dwe; Halisa, Siti Noor; Zahran, Zahran; Zulkipli, Zulkipli; Pratiwi, Diani Ayu; Suriansyah, Ahmad (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Discusses the implementation of the Merdeka Curriculum at SDN Telaga Biru 4 Banjarmasin, which is a refinement of the 2013 Curriculum. Education in Indonesia is experiencing development. The government created an independent curriculum by undertaking a project to raise the prominence of Pancasila pupils who are prepared to meet the difficulties of current developments. The Independent Curriculum provides flexibility for schools and teachers in designing learning according to the characteristics of students. One important aspect of the Merdeka Curriculum is the Pancasila Student Profile Strengthening Program (P5), where students carry out projects to develop their potential and skills. The case study at SDN Telaga Biru 4 shows that the implementation of P5 uses a block system, with the theme of entrepreneurship as the focus. This project involves students in making various types of snacks, helping them develop an entrepreneurial spirit from an early age. Through making snacks, students can understand the importance of food quality for health and use it as a business opportunity in the future. The purpose of this study is to describe how the Project for Strengthening the Profile of Pancasila Students (P5) was implemented with the theme of entrepreneurship. This study employs a qualitative method with a descriptive focus. Interviews are the key data collection approach. Researchers conducted interviews with the Principal and Class I Teachers. The study's findings revealed that the execution of the Project for Strengthening the Profile of Pancasila Students with the topic Entrepreneurship at SDN Telaga Biru 4 went smoothly and with great enthusiasm from the students. The implementation of P5 has the potential to boost student entrepreneurial spirit and teamwork.